Integrasi Sistem Seleksi dan Penempatan Tenaga Kerja Berbasis Kompetensi dalam Struktur Lembaga Pendidikan Islam - Watik; Saiful Hadi; Tobi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This research highlights the transformation of human resource management in Islamic educational institutions from traditional approaches prone to nepotism toward meritocracy-based systems. Although literature on educational staff recruitment has been extensively explored, the integration of modern psychometrics and theological parameters within Islamic educational organizations remains marginalized. This study analyzes six essential selection dimensions: prerequisite rationalization that combines professionalism and morality, Person-Organization Fit calibration, instrument validity, hybrid assessment methodologies, implementation constraint mitigation, and cross-validation strategies. The novelty lies in an integrative framework that synthesizes rational validation metrics with prophetic leadership philosophy (Siddiq, Amanah, Tabligh, Fathanah). The proposed model measures theological integrity and scholarly competence cohesively through instruments with rigorous construct validity, no longer separating technical tests from subjective moral assessments. The implications affirm that precisely validated selection system reconstruction not only reduces placement malpractice but also orchestrates holistic improvement in quality, effectiveness, and competitiveness of Islamic educational institutions